Analysis of blockchain technology - Kashaganova, G. B.; Sekushin, N. S. (Харківський національний автомобільно-дорожній універститет, 2024)
This article provides a brief overview of blockchain technology. Blockchain is a decentralized distributed database that ensures secure and transparent transactions. It allows transactions to occur without the need for third parties. The article gives an example of blockchain technology, explains its basic principles, types, and examples of its use in IT products.
Keywords: blockchain; system; transactions; network; cryptocurrency; bitcoin.; 004